PERAN GREEN VALUE PADA PENGARUH SUSTAINABLE BEHAVIOUR YANG DIMEDIASI OLEH ENVIRONMENTAL SUSTAINABILITY BELIEFS DAN SOCIAL SUSTAINABILITY BELIEFS - Arya Dita Aflaha; Rini Kuswati (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of Green Value on Sustainable Behaviour mediated by Environmental Sustainability Beliefs and Social Sustainability Beliefs. This research method uses a quantitative approach.  The population in this study were students of Universitas Muhammadiyah Surakarta and all circles of society. The sampling technique in this study was non probability sampling with purposive sampling technique. The data collection method used in this research is a questionnaire. In measuring research data using Likert scale. The data analysis technique used in this research is using SMARTPLS. The results of this study are that Green Value has a positive and significant influence on Sustainable Behavior. Green Value has a positive and significant influence on Environmental Sustainability Beliefs. Green Value has a positive and significant influence on Social Sustainability Beliefs. Environmental Sustainability Beliefs have a positive and significant influence on Sustainable Behavior. Social Sustainability Beliefs do not have a positive and significant effect on Sustainable Behaviour. There is a significant effect of Green Value on Sustainable Behaviour mediated by Environmental Sustainability Beliefs. There is no significant effect of Green Value on Sustainable Behaviour mediated by Social Sustainability Beliefs.